Potato leaf senescence affects the olfactory and feeding preferences of the green peach aphid, Myzus persicae - Lopez-Gialdi, Agustín I.; Nussenbaum, Ana Laura; Fernandez, Paula Del Carmen; Segura, Diego Fernando; Fernandez, Patricia Carina; Di Rienzo, Julio; Machado Assefh, Cristina Renata; Álvarez, Adriana E. (Wiley, 2025)
BACKGROUND: Foliar senescence is a physiological process involving the degradation of chlorophyll and proteins, with nitrogen compounds, especially amino acids, mobilised to other parts of the plant. This process enriches the phloem, and improves its nutritional quality for phloem sucking insects like aphids. This study investigated how natural and induced leaf senescence affect the feeding and olfactory behaviour of the green peach aphid (Myzus persicae Sulzer) in potato (Solanum tuberusom L.). Two phenological stages were examined: young plants where senescence was induced in the basal leaves by covering them with a gas-permeable, light-blocking cloth, and mature plants with naturally senescent basal leaves. Chlorophyll and protein levels were quantified to confirm senescence, and volatile organic compounds (VOCs) were identified using gas chromatography–mass spectrometry (GC–MS). RESULTS: Senescence, both natural or induced, reduced chlorophyll and protein levels. In young plants, the induction of leaf senescence tended to increase aphid feeding and olfactory preference. In contrast, in mature plants, aphids consistently preferred non-senescent apical leaves over senescent basal leaves sin both olfactory and feeding assays. Additionally, non-senescent apical leaves of mature plants released significantly higher levels of β-caryophyllene compared to senescent leaves, likely reflecting an overall increase in volatiles emission. CONCLUSION: The results suggest that senescence induction, rather than natural senescence, enhances the nutritional quality of the leaves, allowing aphid propagation. Insights into aphid host preference can be used in future control strategies by promoting agricultural practices that minimise senescence induction caused by factors such as shading due to high sowing density, or nutrient imbalance.